Numerical Evaluation of Climate Scatter Performance of a Cycloidal Wave Energy Converter. Issue 3 (December 2022) - Chitale, Kedar C.; Fagley, Casey; Mohtat, Ali; Siegel, Stefan G.
No abstract available